2008
DOI: 10.1016/j.jacc.2008.04.045
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cigarette Smoking With Enhanced Platelet Inhibition by Clopidogrel

Abstract: Clopidogrel therapy in CS is associated with increased platelet inhibition and lower aggregation as compared with NS. The mechanism of the smoking effect deserves further study and may be an important cause of response variability to clopidogrel therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(134 citation statements)
references
References 10 publications
14
113
3
4
Order By: Relevance
“…Years ago, Bliden et al . conducted a study suggesting that clopidogrel therapy in current smokers was associated with increased platelet inhibition and lower aggregation 20. This research was consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Years ago, Bliden et al . conducted a study suggesting that clopidogrel therapy in current smokers was associated with increased platelet inhibition and lower aggregation 20. This research was consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Bliden et al . proved that the clopidogrel treatment in current smokers was associated with the increased platelet inhibition and the lower aggregation compared with non‐smokers 20. Therefore, cigarette smoking seems to improve the clopidogrel effectiveness.…”
Section: Introductionmentioning
confidence: 96%
“…To date, research on clopidogrel resistance at the molecular level has predominantly focused on gene polymorphisms (9,31,32), rather than associations with miRNA expression in platelets. Testing VASP phosphorylation is a reliable method for the detection of clopidogrel resistance, however it lacks early detection and indicators (20).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this is due to various factors, including clopidogrel resistance, which is attracting increasing concern (6). Clopidogrel resistance is associated with various factors, including individual differences between patients, interactions between drugs, polymorphisms in platelet genes, basic platelet reactivity and platelet sizes (7)(8)(9). However, the molecular mechanism underlying clopidogrel resistance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 Esterases degrade ;85% of absorbed clopidogrel, leaving only ;15% to be converted by the cytochrome P-450 family of enzymes to the active metabolite required for inhibition of the platelet ADP receptor P2Y 12 . 51 Variability in clopidogrel pharmacokinetics and pharmacodynamics has been attributed to a number of factors, including patient noncompliance, absorption (eg, diet or polymorphisms in the transporter molecule ABCB1 54,59,60 ), smoking (which alters cytochrome P-450 levels), 61,62 polymorphisms in CYP2C19, 54-56 drugdrug interactions (eg, proton pump inhibitors [63][64][65] ), intrinsic variation in platelet function before exposure to clopidogrel, [66][67][68] and other clinical factors (obesity, renal dysfunction, diabetes mellitus, age, reduced left ventricular function, inflammation). 58 However, other as-yet unidentified factors also contribute to high ontreatment platelet reactivity.…”
Section: Casementioning
confidence: 99%